PENGARUH KEBIASAAN BEROLAHRAGA TERHADAP NILAI V02MAX PADA REMAJA - Yudiansyah Yudiansyah; Ika Guslanda Bustam (Masker Medika, 2024)
Introduction: VO2max is an indicator of a person's maximum aerobic capacity, which is important for assessing the level of cardiovascular fitness. Objective: This study aims to analyse the effect of exercise habits on VO2max values in adolescents. Method: We conducted VO2max measurements using the Cooper Test, utilizing a quantitative design and experimental approach. We divided the study sample into groups based on the frequency and intensity of their exercise. Results: The analysis results showed that there was a significant effect between exercise habits on VO2max values in adolescents, with the ANOVA test results showing an F value of 19.856 and a significance value of 0.00 (p <0.05). These findings indicate that the more often and intensely a person exercises, the higher the VO2max value achieved. Conclusion: This study concludes that routine and regular exercise habits significantly increase adolescents' aerobic capacity, which can ultimately contribute to improving cardiovascular health and overall fitness.